PENGARUH KUALITAS PRODUK, PERSEPSI HARGA DAN PROMOSITERHADAP KEPUASAN PELANGGAN (Studi PadaPelanggan Nutrition ClubMariane Di Kudus) - Endah Sulistiani, 14.05.51.0066; Tjahjaningsih,, Endang (Students' Journal of Economic and Management, 2018)
The purpose of this research is described and analyze the influence of the product quality ,Price Perceptionand specific economic campaign to promote bos program against customer satisfaction in drinking water nutrition club marriane in the holy city .In this research variables reaches as high as free that affects a decision which was made of the eye is lined on the variables of pt indofood acquired misp shares the product quality , Price Perception, and promotion . Percent of the population in this research is the customer nutrition club marriane in the holy city.And that we have been selected as many as 100 the number of respondents who he sets up as a sample.The technique of the examination of that is used in a working meeting with the practical teaching exam participants from the analysis factors other than a fuel , reliability test with cronbach alpha , it is anticipated that analysis linear regression of multiple , and test it significance of the koefesien of determination to attest the truth of a hypothesis . The results of the testing obtained that there is significant influence variables reaches as high as the product quality against customer satisfaction in drinking water.There are significant influence variables reaches as high as Price Perception has customer satisfaction in drinking water.There are significant impact variables reaches as high as campaign to promote bos program against customer satisfaction in drinking water . Key words: Quality products ,Price Perception and promotion of customer satisfaction